2022
DOI: 10.1186/s12920-022-01414-6
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an lncRNA model for prognostic prediction of bladder cancer

Abstract: Objective We aimed to investigate the role and potential mechanisms of long non-coding RNAs (lncRNAs) in bladder cancer (BC), as well as determine their prognostic value. Methods LncRNA expression data and clinical data from BC patients were downloaded from The Cancer Genome Atlas (TCGA) database. R software was used to carry out principal component analysis (PCA), differential analysis, and prognostic analysis. Lasso regression and multivariate Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…DTNA encodes a protein component of the dystrophin-associated protein complex, and mutations in this gene are primarily associated with left ventricular dystrophy. Current studies have also shown that DTNA is associated with bladder cancer ( Shi et al, 2022 ), liver cancer ( Hu et al, 2020 ), oesophageal cancer ( Fu et al, 2021 ) and colorectal cancer ( Liu et al, 2018 ). In bladder cancer, overexpressed DTNA functions as an oncogene and, along with four other genes, forms a diagnostic model for detecting recurrence and prognosis ( Shi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTNA encodes a protein component of the dystrophin-associated protein complex, and mutations in this gene are primarily associated with left ventricular dystrophy. Current studies have also shown that DTNA is associated with bladder cancer ( Shi et al, 2022 ), liver cancer ( Hu et al, 2020 ), oesophageal cancer ( Fu et al, 2021 ) and colorectal cancer ( Liu et al, 2018 ). In bladder cancer, overexpressed DTNA functions as an oncogene and, along with four other genes, forms a diagnostic model for detecting recurrence and prognosis ( Shi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have also shown that DTNA is associated with bladder cancer ( Shi et al, 2022 ), liver cancer ( Hu et al, 2020 ), oesophageal cancer ( Fu et al, 2021 ) and colorectal cancer ( Liu et al, 2018 ). In bladder cancer, overexpressed DTNA functions as an oncogene and, along with four other genes, forms a diagnostic model for detecting recurrence and prognosis ( Shi et al, 2022 ). However, in esophageal cancer, low expression levels of DTNA were negatively correlated with miR-301b and positively correlated with the prognosis of esophageal cancer patients, suggesting an anti-oncogene role ( Fu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To further refine potential core genes, intersected genes were submitted to the STRING database (https:// cn.string-db.org/) [15]. Protein interaction data were exported to Cytoscape (version 3.4.0), where the cyto-Hubba plugin was employed for ranking nodes within the network based on their network features.…”
Section: Protein-protein Interaction Networkmentioning
confidence: 99%